Students’ Viewpoint to the Environment and Health - Matulienė, Gražina (Sociologija. Mintis ir veiksmas, 2003)
From the psychological point of view in explaining and predicting behaviour the most effective way is to find links between perceived seriousness of pollution problems, general environmental evaluation, world ecological problems and self-reported proenvironmental behaviours. Sometimes evaluation of environmental events depend upon more general orientations. In this connection the main task of investigators would be to discover what people know about main environmental problems, how do they perceive and evaluate them and how the events are related to their social life. That is why the person in the environment approach was used in the research. On the other hand the information and knowledge serve as a bases for development of environmental viewpoints. For that reason in the process of the research it was necessary to find out the level of knowledge related to the environmental events. In the future students/respondants who have participated in the research are going to became high quality specialists and they will be responsible for person-environment conditions in general: planning of houses, residences, and areas for recreation, management of toxic products and waste, protection of human health conditions, person-environment relationship, decision making processes, related to pollution of the environment. For the above mentioned reasons the decision was made to study the students many-sided viewpoints to the environment.
Keywords: environment; attitude; worry; individual traits